2014
DOI: 10.4161/org.29055
|View full text |Cite
|
Sign up to set email alerts
|

From the cytoplasm into the cilium: Bon voyage

Abstract: The primary cilium compartmentalizes a tiny fraction of the cell surface and volume, yet many proteins are highly enriched in this area and so efficient mechanisms are necessary to concentrate them in the ciliary compartment. Here we review mechanisms that are thought to deliver protein cargo to the base of cilia and are likely to interact with ciliary gating mechanisms. Given the immense variety of ciliary cytosolic and transmembrane proteins, it is almost certain that multiple, albeit frequently interconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
74
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 199 publications
0
74
0
3
Order By: Relevance
“…Since the the IFT proteins, such as IFT46, are localized in trans-Golgi network (TGN)-derived vesicles during flagellar regeneration, Woods et al have suggested that IFT complexes may associate with the vesicle first, recruit the cargos, and then be targeted to the basal body (Wood and Rosenbaum, 2014). Many ciliary proteins, especially ciliary membrane proteins, contain ciliary-targeting sequences (CTSs) (Bhogaraju et al, 2013;Malicki and Avidor-Reiss, 2014). These CTSs mediate the basal body and ciliary localization of target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Since the the IFT proteins, such as IFT46, are localized in trans-Golgi network (TGN)-derived vesicles during flagellar regeneration, Woods et al have suggested that IFT complexes may associate with the vesicle first, recruit the cargos, and then be targeted to the basal body (Wood and Rosenbaum, 2014). Many ciliary proteins, especially ciliary membrane proteins, contain ciliary-targeting sequences (CTSs) (Bhogaraju et al, 2013;Malicki and Avidor-Reiss, 2014). These CTSs mediate the basal body and ciliary localization of target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some ciliopathy patients display a range of neurological disorders including cognitive deficits (Lee and Gleeson, 2011), thereby highlighting the importance of primary cilia function within the brain (Green and Mykytyn, 2010). Let us briefly describe some main structural features of these crucial appendages and then some of their possible functional implications, while for a more detailed description, the reader is referred to several excellent reviews that have been recently published (Louvi and Grove, 2011;Guemez-Gamboa et al, 2014;Malicki and Avidor-Reiss, 2014). The primary cilium is about 1-5 microns in length and only 200-300 nm in diameter and consists of a ciliary membrane that surrounds an axoneme, composed of nine microtubule pairs (the 9+0 configuration) anchored to a microtubule organizer, the ciliary basal body (Louvi and Grove, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The limiting factor is mainly the steric hindrance; hence, proteins > 9 nm in diameter are restricted from entering the cilia. Furthermore, it has been shown that cilia proteins can have specialized sequences, the ciliary targeting sequences, which direct the proteins to the ciliary compartment (Malicki and Avidor-Reiss, 2014). Thus, the primary cilium is a sensing organelle functionally separated from the cytoplasm by the ciliary base, which controls the selective entry of ciliary proteins (Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The dendrite of many of these neurons is composed of two parts: the inner segment and the sensory cilium (Keil 1997;Swaroop et al 2010) ( Figure 1A). The sensory cilium is composed of a connecting cilium, which is a specialized ciliary transition zone (Malicki and Avidor-Reiss 2014), and an outer segment, which houses the sensory transduction machinery . The main body of the dendrite, referred to as the inner segment, serves as a link between the neuronal cell body and the sensory cilium.…”
mentioning
confidence: 99%
“…Second, mutations affecting the connecting cilium, such as cep290 (den Hollander et al 2006;Cideciyan et al 2007;Basiri et al 2014), and sensory cilium, such as intraflagellar transport (IFT) proteins, have a similar effect in both human photoreceptor and Drosophila sensory function (Avidor-Reiss et al 2004;Crouse et al 2014). Third, the connecting cilium of both D. melanogaster mechanosensory neurons and human photoreceptors is uniquely long and serves as the connection between two bulky compartments: the inner and outer segments, which display much greater width and volume compared to the transition zone itself (Malicki and Avidor-Reiss 2014). This is likely to impose unusual structural requirements.…”
mentioning
confidence: 99%